Religiosity and University Students’ Attitudes About Vaccination Against COVID-19 - Petrović, Jelena R. (Religions, 2025)
During the COVID-19 pandemic; it transpired that there were different influences contributing to the people’s (un)willingness to be vaccinated. In our research, we start from the assumption that religiosity may be one of the reasons for such behaviour. The online snowball sample covered 361 students of the teacher education faculties in Serbia. The questionnaire consisted of questions referring to the attitudes about vaccination and the questionnaire about religiosity. The independent variable was the level of the students’ religiosity, while the dependent variables referred to their attitudes about vaccination. The data were processed with the aid of non-parametric and descriptive statistics and ANOVA. The results showed that there were differences in the students’ attitudes about vaccination and that the level of religiosity had an important role in the shaping of the students’ awareness of the importance of vaccination. Thus, the starting hypothesis was confirmed that religiosity is one of the factors of influence contributing to the formation of the attitudes about vaccination against COVID-19, which affected the health-risky behaviour among young people during the pandemic of this disease.